Salivary glucose levels and estimation of food intake in type 2 diabetes mellitus patients - Sri Tjahajawati; Angievel Chandra; Anggun Rafisa (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Saliva, an easily collectible organic fluid, offers a noninvasive means for multiple samplings to determine salivary glucose levels, comparable to blood and potentially helpful in diagnosing and monitoring type 2 diabetes mellitus. Purpose: This research was carried out to determine the value of salivary glucose levels and food intake in patients with type 2 diabetes mellitus. Methods: This research utilized a descriptive quantitative method with a cross-sectional approach. The study population comprised type 2 diabetes mellitus patients in Bandung and Jatinangor. The samples, consisting of 27 individuals from each group—type 2 diabetes mellitus patients and healthy participants—were collected through purposive sampling. Saliva was collected using the spitting method and measured to determine salivary glucose levels (mg/dL). Food intake per day (in grams) was assessed using a semi-quantitative food frequency questionnaire and converted using NutriSurvey 2007. Results: Among the 27 participants with type 2 diabetes mellitus, salivary glucose levels were found to be ≥2 mg/dL (mean 23.47 mg/dL), whereas in the healthy group, 5 participants (18.5%) exhibited salivary glucose levels <2 mg/dL (mean 8.29 mg/dL). Most type 2 diabetes mellitus patients and healthy participants reported food intake below the Indonesian dietary recommendations. Conclusion: In our limited sample, salivary glucose levels in type 2 diabetes mellitus patients were higher compared to healthy participants. Energy intake in both groups showed similar results. Salivary glucose levels and BMI exhibited a correlation, though notably weak in this study.